Deletion of RAP1 affects iron homeostasis, azole resistance, and virulence in Candida albicans - Min-Chi Yang; Wei-Luen Huang; Hsuan-Yu Chen; Shin-Huey Lin; Yu-Shan Chang; Kuo-Yun Tseng; Hsiu-Jung Lo; I-Ching Wang; Chi-Jan Lin; Chung-Yu Lan (mSphere)
ABSTRACT Rap1 is a DNA-binding protein conserved from yeast to mammals for its role in telomeric maintenance. Here, to explore additional functions of Candida albicans Rap1, we performed RNA sequencing analysis. Experimental validations further showed that Rap1 plays a role in iron regulation, especially under low-iron conditions. Moreover, Rap1 was involved in iron acquisition and modulation of iron-related genes. Rap1 was found to be associated with fluconazole resistance in a low-iron condition. Finally, we demonstrated that the deletion of RAP1 leads to reduced C. albicans virulence in a mouse model of infection. Together, this study reveals new functions of C. albicans Rap1, particularly in iron homeostasis, azole resistance, and virulence.IMPORTANCECandida albicans is an important pathogenic fungus that can cause superficial to life-threatening infections. Iron is essential for almost all organisms, yet it is highly restricted within the human host to defend against pathogens. To grow and survive in the iron-limited host environment, C. albicans has evolved multiple iron acquisition mechanisms. Understanding the regulation of iron homeostasis is, therefore, critical for elucidating C. albicans pathogenesis and virulence. This study explores the novel functions of C. albicans Rap1, with a focus on its contribution to iron acquisition and utilization. Our findings further highlight how iron availability impacts antifungal resistance and virulence through Rap1, providing insight into the complex iron regulatory machinery of C. albicans.